Purchasing Decisions Effect of Social Media Marketing, Electronic Word of Mouth (eWOM), Purchase Intention - Buyung Romadhoni; Akhmad Akhmad; Naldah Naldah; Niluh Putu Evvy Rossanty (Journal of Accounting and Finance Management, 2023)
This research aims to examine the effect of social media marketing and e- word of mouth on purchasing decisions; social media marketing and e-word of mouth influence purchase intention; social media marketing and e-word of mouth influence purchasing decisions by mediating purchase intention. This study uses a quantitative descriptive research approach using data obtained from a sample of the study population and analyzed according to statistical methods. The population in this study uses an infinite population, where the infinite population in this study is taken from consumers who have purchased Zoya's hijab products. The sampling technique used was accidental sampling with a total sample of 70 respondents. The analysis technique used is path analysis technique. by collecting data through research instruments, by distributing questionnaires to consumers. The results of the study found that based on the results of the study found that social media marketing and e-word of mouth had a positive effect on purchasing decisions; social media marketing and e-word of mouth have a positive effect on purchase intention; social media marketinghas a positive effect on purchasing decisions through mediation of purchase intention; e-word of mouth has a positive effect on purchasing decisions through purchase intention. social media marketinghas a positive effect on purchasing decisions through mediation of purchase intention; e-word of mouth has a positive effect on purchasing decisions through purchase intention. social media marketing has a positive effect on purchasing decisions through mediation of purchase intention; e-word of mouth has a positive effect on purchasing decisions through purchase intention.